A comparative study of construction waste generation rate based on different construction methods used in construction projects in Malaysia - Maniam, Haritharan (2019)
In Malaysia, the huge generation of construction waste (CW) has led to negative impact on the environment. Limited data is available on quantification methods of CW in the country. The lack of quantification methods has resulted to the improper management of CW. The consequence of the improper CW management has shortened the lifespan of landfills. The aim of this study is to compare the construction waste generation rate between different construction methods. In order to obtain CW data in terms of volume and weight, the site visit (SV) method was carried out for a 3-month period. There are two types of SV methods applied in this study, namely direct measurement and indirect measurement. The data were collected from 12 social amenities projects at the construction stage which can be divided into the Conventional Construction Method (CCM), the Mixed Construction Method (MCM) and the Industrialised Building System (IBS). The waste (tonnes) obtained from each construction method is divided by gross floor area (m2) to attain the Waste Generation Rate (WGR). Finally, the result of the study revealed that the WGRs for IBS, MCM and CCM are 0.018 tonne/m2, 0.030 tonne/m2 and 0.046 tonne/m2 respectively. It can be concluded that the IBS method is the most effective method to reduce CW generation on site. This finding will be a contribution for construction players, policy makers and authorities in the country to promote IBS methods more rigorously.